Impact of Thermal Annealing under Nitrogen Ambient on Structural, Micro-Raman, and Thermogravimetric Analyses of Camphoric-CNT - M. S. Shamsudin; A. B. Suriani; S. Abdullah; S. Y. S. Yahya; M. Rusop (Journal of Spectroscopy, 2013)
A systematical study of the effects on thermal annealing treatment under nitrogen ambient on the structural, micro-Raman, and thermogravimetric analyses of camphoric-carbon nanotubes (CNT) has been undertaken. Heat treatment of camphoric-CNT under nitrogen ambient was found to be an efficient technique of removing noncrystalline carbon and residual transition metal. Based on structural analysis, the heat-treated samples showed a clear view of overall camphoric-CNT structure.